Enabling Dual‐Ion Batteries via the Reversible Storage of Pyr14+ Cations into Coronene Crystal. Issue 6 (26th April 2020) - Fang, Yaobing; Bi, Wanying; Wang, Aiye; Zheng, Wen; Yuan, Wenhui; Li, Li
Abstract : Dual‐ion batteries with pure ionic liquid electrolyte (IL‐DIBs) have received increasing interest due to their sustainability, high operating voltage, and environmental friendliness. However, owing to the insertion/extraction of large‐size ionic liquid cations, the conventional IL‐DIBs with a graphite anode suffer from severe volume expansion and graphite exfoliation on the anode, causing a poor cycling performance. Herein, a novel IL‐DIB is constructed by introducing a bulk organic material (coronene) as the anode, against a natural graphite cathode. The results show that, in a voltage window range from 1.0 to 4.4 V, the battery has a high discharge specific capacity of ≈73.3 mA h g −1 and exhibits a good cycling performance for 450 cycles with a lower capacity loss of 0.061 mA h g −1 per cycle at a current density of 300 mA g −1 (3 C). Notably, it still maintains a considerable capacity of ≈55.8 mA h g −1 at a high rate of 10 C. In addition, the reversible intercalation/de‐intercalation of the Pyr14 + cations into/from the coronene anode is investigated by ex situ X‐ray diffraction and Fourier transform infrared spectroscopy, showing an excellent structure stability of the coronene crystal during the charge–discharge process. Abstract : An organic/graphite dual‐ion battery with ionic liquid electrolyte is fabricated using coronene as the anode material, and with graphite as counter electrode. The battery shows excellent cycling performance, and obtains a high initial discharge specific capacity of ≈73.3 mA h g −1 at 3 C (1 C = 100 mA g −1 ), outperforming most of the dual‐graphite batteries using ionic liquid as electrolyte.